Development of Macromedia Flash Learning To Improve Intensive Listening Ability - Rambe, Nana Ronawan; Ely, Dewi Qhuril Malasari (Jurnal Teknologi Informasi dan Pendidikan, 2023)
This study aimed to produce learning media through Macromedia Flash software program to improve the ability to listen to incentives on fantasy story material in class VII SMP Negeri 4 Central Maluku. The subjects of this study were the seventh grade students of SMP Negeri 4 Central Maluku, totaling 28 people. This study used a development method adapted from the Borg and Gall development model. The resulting media consists of three parts, namely the opening (covering SK, KD, and instructions for using media), content (covering material menus, exercises, and quizzes), and closing (covering motivational videos and author biodata). The macromedia flash learning media was tested on (1) learning media experts and (2) material experts, (3) practitioners, and (4) students. The instruments used in this research are material expert questionnaires, media expert questionnaires, practitioner and student response questionnaires, and intensive listening indicator instruments. The method used in data collection is observation, interviews, and questionnaires. The stages carried out in this research include: (1) Design stage, making media using Macromedia Flash application with the help of Ms. Power Point, and (2) design validation, (3) product revision, and (4) product testing on students of SMP Negeri 4 Maluku Tengah in grade VII. Based on the test results obtained from the expert test questionnaire, it shows that macromedia flash is feasible and ready to be implemented.